GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENCAPAI AKREDITASI A ( STUDI KASUS PADA SDN 24 LUAK BAYAU SULIT AIR KECAMATAN X KOTO DIATAS KABUPATEN SOLOK ) - Hardianto Hardianto (IAIN Batusangkar, 2020)
Leadership style is pattern, method or action taken by a leader in affecting, moving, encouraging subordinates to work voluntarily to achieve the organitation objectives. The purpose of this study is to describe the style of leadership of SDN 24 Luak Bayau Sulit Air in achieving accreditation A. The kinds of research is describtion research with desain cases study. Data study were collected through interviews and documentation. The data collection technique used was snowball sampling. Data validity is tested through sourch triagulation. Sources and data analysis is done through a process of (1) data reduction, (2) Display of data, and (3) conclusion.The results showed the prinsipals leadership stayle SDN 24 Luak Bayau in achieving A accreditation is democratic leadership stayle and partisipatif leadership stayle, task oriented and human relation leadership stayle.